1978
DOI: 10.1107/s0567739478001254
|View full text |Cite
|
Sign up to set email alerts
|

X-ray study of the atomic charge densities in MgO, CaO, SrO and BaO

Abstract: Accurate X-ray structure factors of CaO, SrO and BaO were measured at 293 K from single crystals and analysed together with the data of Sanger [Acta Cryst. (1969), A25, 694-702] on MgO. The oxygen ion is seen to suffer an average compression and a fourth-order cubic harmonic type deformation, as compared to the atomic superposition model, yielding a lower average charge density in the surrounding region and a charge transfer from [ 111 ] to the [ 100] direction. These features strengthen with increasing atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 22 publications
7
20
0
Order By: Relevance
“…Interionic charge transfer was found, resulting in ionic charges of AE1:36e. In spite of the large uncertainty in the charges resulting from the large correlation in the refinement, these values are close to the charges obtained by direct integration of the ED by Vidal-Valat et al [56]: þ1:36e cation and À1:14e anion and agree well with the results of a model K refinement of the ED of the MgO molecule [61]. Nevertheless, the value of the mean inner-cell electrostatic potential, 15:05 V calculated from the model of the ED according to reference [62], is between the holographic experimental value of 13:01 V and the neutral-atom procrystal value of 18:41 V. This means that the ionicity of the bond in MgO crystal is underestimated by the K model fitted to the X-ray structure amplitudes [63].…”
Section: Alkaline-earth Seriessupporting
confidence: 87%
See 1 more Smart Citation
“…Interionic charge transfer was found, resulting in ionic charges of AE1:36e. In spite of the large uncertainty in the charges resulting from the large correlation in the refinement, these values are close to the charges obtained by direct integration of the ED by Vidal-Valat et al [56]: þ1:36e cation and À1:14e anion and agree well with the results of a model K refinement of the ED of the MgO molecule [61]. Nevertheless, the value of the mean inner-cell electrostatic potential, 15:05 V calculated from the model of the ED according to reference [62], is between the holographic experimental value of 13:01 V and the neutral-atom procrystal value of 18:41 V. This means that the ionicity of the bond in MgO crystal is underestimated by the K model fitted to the X-ray structure amplitudes [63].…”
Section: Alkaline-earth Seriessupporting
confidence: 87%
“…The trend of ionic character in alkaline-earth oxides: MgO < CaO < SrO < BaO is supported by the interpretation of several experiments like X-ray measures of charge density [55,56,69], elastic constants [309], infrared spectroscopy [310] and indirectly by experiments in heterogeneous catalysis [294,295,311], low-energy D þ scattering [312] and band-structure calculations [216,313]. On the other hand, cluster model [292] and PP-DFT-LDA [226] [226] From the cluster-model calculations, Pacchioni et al [292,313] concluded that the decrease of the lattice Madelung potential and the involvement of the low-lying d levels of the cations play an important role in the covalent orbital hybridization.…”
Section: Correlation Betweenmentioning
confidence: 76%
“…In [7,9, 151 a much more complex model is suggested, according to which the cation is assumed to be doubly charged (Mg"), while an effective charge Q = -1 (in electron charge units) is attributed to the anion. The latter model agrees with the X-ray scattering data [16].…”
Section: Introductionsupporting
confidence: 71%
“…In the present paper the values of radii, close to the empirically obtained radii of the "best separation" for MgO [16] were used. It is important to note that the empirical values of radii given in [16] correspond to the overlap of anion and cation spheres. In the present paper the standard MT-approach providing tangent spheres was used.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…It is now a common practice (Coppens, 1977;Dawson, 1967;Fink, Gregory & Moore, 1976;Harel & Hirshfeld, 1975;Kohl & Bartell, 1969;Price, Varghese & Maslen, 1978;Stevens, 1979;Stewart, 1976;Vidal-Valat, Vidal & Kurki-Suonio, 1978) for molecular electron densities derived from X-ray and electron diffraction data to be expressed as a superposition of pseudoatom densities centred on each of the nuclei of the molecule. By denoting the nuclear position vectors as R a and the associated pseudoatom density as p~ the total density becomes p(r)= ~Pa(r--Ra): ~.pa(ra).…”
Section: Introductionmentioning
confidence: 99%